Challenges in staging and surveillance of patients with neurofibromatosis and cutaneous malignant melanoma. (September 2019) - Chew, P.R.; Toh, V.V.; Kotwal, A.
Summary: Malignant melanoma is a skin neoplasm with a rising trend of incidence. Positron Emission Tomography in combination with Computed Tomography (PET-CT) imaging is an essential diagnostic tool for both staging and surveillance of melanoma patients; especially in metastatic disease, where prognosis is poor. We report a case of a patient with known Neurofibromatosis type 1 (NF-1) who presented to the Skin Cancer Multidisciplinary meeting with 11 mm Breslow thickness malignant melanoma of the left forearm. His extensive dermal neurofibromatoses proved a diagnostic challenge to the team. There have been published studies linking NF-1 with malignant melanoma. However the incidence and significance of this has yet to be established. We also discuss the use of PET-CT imaging and skin surveillance in the monitoring and staging of this patient.